Summaries in English - Thordis J. Sigurðardóttir; Hildigunnur Ólafsdóttir; Wenche Blomberg; Paul Larsson; Dorthe Borggaard Kristoffersen (Nordisk Tidsskrift for Kriminalvidenskab)
Summaries in English